Antiviral Therapy in Corona Virus Disease-19 (Covid-19) - Laisa Azka; Irvan Medison; Dessy Mizarti (Biomedical Journal of Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) is a disease caused by a new coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, previously known as 2019-nCoV), which was first identified in Wuhan City, Hubei Province, PRC. The total number of COVID-19 cases worldwide has reached 102 million cases with 54 million cases recovered and 2.3 million cases dead. Handling for this pandemic is still being carried out. In Indonesia, the antiviral drugs used are those that meet the Emergency Use Authorization (EUA) requirements, and are included in the COVID-19 management guidelines issued by the Ministry of Health. Antiviral options used are Oseltamivir, Favifirapir, Remdesivir. Until now, the use of antivirus is still being researched regarding the effectiveness and security of the antivirus used. Oseltamivir is used as an antiviral for COVID-19 with a mild clinical course, Favifirapir is used for mild to moderate clinical cases of COVID-19. For the use of remdesivir in COVID-19 patients with severe and critis clinical conditions.